PENGEMBANGAN APLIKASI PENGGALANGAN DANA MENGGUNAKAN KONSEP CROWDFUNDING BERBASIS MOBILE PADA PESANTREN AL-QUR’AN MAFATIH - Effendi, Muhammad Ridwan; Narji, Mohammad; Saputra, Yan Sofyan Andhana (Universitas Dirgantara Marsekal Suryadarma, 2021)
AbstractMafatih Al-Qur'an Islamic Boarding School is located in Purwakarta, West Java. This Islamic boarding school is under the Mafatih Global foundation. Mafatih Al-Qur'an Islamic Boarding School has 120 students. As of now, there are 6420 donors and there is 2000m of land. This pesantren does not attract education funds for underprivileged or underprivileged students. The operational costs of the pesantren, apart from students who can afford it, also come from donations from donors as well as waqf funds from donors. Funds from waqf are used to provide facilities and infrastructure for pesantren. The objectives of the research to be achieved are applying the crowdfunding concept in raising funds at the Mafatih Al-Qur'an Islamic Boarding School and designing a mobile-based fundraising crowdfunding application at the Mafatih Al-Qur'an Islamic Boarding School with the crowdfunding concept. The development method used in this research is Scrum. According to Rising and Janoff (2000), Scrum is a software development method that gradually develops software in a complex environment. Scrum divides the roles in its method into 3, namely the product owner, scrum master and the development team (Schwaber and Sutherlad 2017). The stages of Scrum work begin with a sprint planning meeting which is held at the beginning of the sprint, then continue with the daily scrum which is the stage of making program code in this study, at the end of the sprint a sprint review meeting and a sprint retrospective are held (Pressman, 2010). The last is the results and targets of the research in the form of a mobile-based application in raising funds from outside parties that can be installed on mobile phones. With the mobile-based application, it is hoped that it will make it easier for donors to donate funds quickly and effectively.Â Keywords: Application, Fundraising, Crowdfunding Concept, Mobile Based